An investigation of 10 Y-STR loci and the detection of specific haplotype frequencies in Turkish population - Rüstemoglu, Aydın; Akay, Güvem G.; Karabulut, Halil G.; Kadıkıran, Ahmet; Bökesoy, Işık (Scientific Research Publishing, 2011)
This study is to survey 10 Y-STR loci in 241 males from Turkey. In this study, the 241 healthy and unrelated males living in different parts of Turkey for at least three generations were included. Genomic DNAs were isolated from peripheral blood samples by standard phenol-chloroform extraction method. 10 Y-STR loci including DYS19, DYS385a/b, DYS388, DYS389I/II, DYS390, DYS391, DYS392, DYS393, and YCAIIa/b were analyzed by using PCR and denaturing PAGE. Allele frequencies, gene diversities and haplotype frequencies were analyzed. Gene diversity per locus varied from 0.5788 (DYS388) to 0.8903 (DYS385a/b). The numbers of haplotypes in minHt recommended by YCC and Ht10 have been 208 and 186, respectively. When our minHt haplotypes frequencies compared with the other seven populations, we have found statistically significant differences between our results and other populations (P < 0.01) except that Czech population (P > 0.05). We suggest that an alternative haplotype designated as aHt maybe alternative to minHt in respect of its Y-STR content with the highest gene diversity value. The aHt haplotype has found a higher discriminatory potential than minHt haplotype with a better Pd combined value (0.9999936 vs 0.9999836) and has higher average gene diversity per locus (0.7834 vs 0.7518) in Turkish population. aHt haplotype can be proposed as an alternative to minHt in paternity testing and forensic medicine applications involving Turkish male population. This study has also provided additional information to the framework of variation involving 10 Y-STR loci as well as a further contribution to the Y-STR database for Turkish male population.
Keywords: Y Chromosome; Y-STR; Polymorphism; Ha- plotype; Turkey